Key candidate genes associated with BRAFV600E in papillary thyroid carcinoma on microarray analysis. Issue 12 (3rd June 2019) - Yu, Xiaqing; Zhong, Peng; Han, Yali; Huang, Qingqing; Wang, Jian; Jia, Chengyou; Lv, Zhongwei
Abstract: The mechanisms of B‐type Raf kinase (BRAF) V600E mutation in papillary thyroid cancer (PTC) remain to be elucidated. With the aim to investigate the key candidate genes distinctive to BRAF V600E ‐PTC, we analyzed the transcriptomics data from three microarray datasets (GSE27155, GSE54958, and GSE58545) and identified 491 differentially expressed genes (DEGs) between BRAF V600E ‐PTC and BRAF wild type ‐PTC. Functional enrichment analysis of DEGs revealed that negative regulation of wound healing may be involved in the BRAF V600E ‐related pathogenesis in PTC. Weighted gene coexpression network analysis revealed BRAF V600E ‐related coexpressed genes in PTC, from which hub genes were selected. The intersection of DEGs and hub genes revealed 31 candidates, wherein GRB7, SNAP25, SLC35F2, FAM155B, HGD, and ITPR1 were rendered the key candidate genes via receiver operating characteristic curve analysis. On further characterization, the six key genes displayed significantly different expression patterns at different cytomorphology, however, with no significant difference in overall survival. These results provide novel insights into the key genes distinctive to of BRAF V600E in PTC and might be suggestive as therapeutic targets for further application. Abstract : This study aimed to investigate the role of BRAF V600E in papillary thyroid cancer (PTC) via analysis of transcriptomics data from three microarray datasets. We found that six key genes ( SLC35F2, GRB7, SNAP25, ITPR1, FAM155B, and HGD ) are potentially involved in the regulatory mechanism of BRAF V600E ‐induced signaling in PTC via differentially expressed genes screening and weighted gene coexpression network analysis.